2016
DOI: 10.1126/scisignal.aab2820
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of NF-κB p65 activity by serine 536 phosphorylation

Abstract: Nuclear factor κB (NF-κB) is a master regulator of inflammation and cell death. Whereas most of the activity of NF-κB is regulated through the inhibitor of kB (IκB) kinase (IKK)–dependent degradation of IκB, IKK also phosphorylates subunits of NF-κB. Here, we investigated the contribution of the phosphorylation of the NF-κ B subunit p65 at the IKK phosphorylation site serine 536 (Ser536) in humans, which is thought to be required for the activation and nuclear translocation of NF-κB. Through experiments with k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 43 publications
(75 reference statements)
5
65
0
Order By: Relevance
“…In our study, we showed that CDK7 inhibition suppressed NF‐κB signalling pathway activation and p65 nuclear translocation in RA FLS (Figs and ), indicating that reduction of IL‐1β/IL‐6 secretion by CDK7 inhibition might be due to NF‐κB signalling pathway blockage. Furthermore, besides phosphorylation and subsequent degradation of inhibitory molecular, protein kinases are also required for optimal NF‐κB activation by targeting functional domains of NF‐κB protein themselves . Our data also displayed that CDK7 inhibitor BS‐181 greatly decreased the phosphorylation of p65 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we showed that CDK7 inhibition suppressed NF‐κB signalling pathway activation and p65 nuclear translocation in RA FLS (Figs and ), indicating that reduction of IL‐1β/IL‐6 secretion by CDK7 inhibition might be due to NF‐κB signalling pathway blockage. Furthermore, besides phosphorylation and subsequent degradation of inhibitory molecular, protein kinases are also required for optimal NF‐κB activation by targeting functional domains of NF‐κB protein themselves . Our data also displayed that CDK7 inhibitor BS‐181 greatly decreased the phosphorylation of p65 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…kinase-1, and the interaction between NF-kB p65 and mitogen-and stress-activated protein kinase-1 results in fully functional NF-kB, which can recruit transcriptional coactivators, such as p300 and CREB-binding protein, to drive transcription of NF-kB-regulated genes (61)(62)(63). To further investigate whether BGLF2 affects the phosphorylation of p65, HEK293T cells were transfected with either plasmid pBGLF2-Flag or vector control pFlag-N1.…”
Section: Bglf2 Restrains P65 (Ser536) Phosphorylationmentioning
confidence: 99%
“…An IκB-independent, alternative NF-κB pathway (altNF-κB) exists that involves the activation of RelB-p52 heterodimers by IKKα-induced proteolytic cleavage of p100 into p52 (3). Additionally, phosphorylation of a pool of IκB-independent p65 on Ser536 has been reported to result in p65-p65 homodimer formation and activation of genes distinct from cNF-κB activation (6); however, recent evidence suggests this modification serves as a brake on p65-dependent transcription (7).…”
Section: Introductionmentioning
confidence: 99%